HRM analysis provides insights on the reproduction mode and the population structure of Gnomoniopsis castaneae in Europe. (11th July 2016) - Sillo, F.; Giordano, L.; Zampieri, E.; Lione, G.; De Cesare, S.; Gonthier, P.
Abstract : Gnomoniopsis castaneae is an emergent nut rot agent of chestnut in southern Europe. To elucidate its population genetics, three simple sequence repeat (SSR) and two hypervariable markers were developed and assessed through high‐resolution melting (HRM) analysis on 132 isolates collected from 10 sites in Italy, France and Switzerland. High allele diversity (ranging from 0.23 to 0.40 depending on site) and number of haplotypes (49) were observed. More than 70% of the molecular variance could be accounted among isolates within sites. Multilocus analysis showed absence of linkage disequilibrium, suggesting a predominant role played by sexual reproduction and random mating. Data analyses indicated the presence of at least two putative distinct subpopulations and this was confirmed by several approaches, including analysis of shared haplotypes, multivariate and Bayesian analyses. Based on data of allelic diversity, the possibility that the pathogen could have been introduced is discussed. This work assessed the genetic variability and the sexual strategies of G. castaneae in Europe, adding useful information on the epidemiology of this fungal plant pathogen.